Physics Education Students' Understanding of X-Ray Concepts and Applications: An Interview Study on Stambuk Students 2021 - Sembiring, Grace Kania Violentina; Fadilah, Nurul; Sitio, Apri Ananta (Golden Ratio of Data in Summary, 2025)
This research aims to explore the understanding of Physics Education students of the class of 2021 regarding the concept and application of X-rays in various fields. Through a qualitative approach with an in-depth interview method, this study involved three participants to gain insight into their understanding of the basic principles of X-rays, the formation process, as well as aspects of radiation safety and risk. The results show that although students have a basic understanding of X-rays as electromagnetic radiation, there are misconceptions about the scope of their application and the principles of physics that underlie the formation of X-rays. The study also found limitations in lecture materials in emphasizing aspects of radiation protection and its applications outside the medical world, which is important to strengthen a comprehensive understanding. Based on these findings, the study provides recommendations to develop a more applicable curriculum, improve practicum facilities, and integrate cross-disciplinary studies so that students have a broader understanding of X-rays.